Just Grace and the double surprise - Harper, Charise Mericle (Boston Houghton Mifflin, 2011)
While Grace and her best friend Mimi are waiting for the arrival of the baby sister Mimi's family plans to adopt, Grace gets a big surprise.
b
b
Keywords: Best friends -- Fiction; Friendship -- Fiction; Siblings -- Fiction; Dogs -- Fiction; Schools -- Fiction